Uji Model Aermod Terhadap Emisi di PT. X Jawa Timur - Syadzadhiya Qothrunada Zakiyayasin Nisa; Diva Yanuar Pramana Putra (Prosiding ESEC, 2023)
This study aims to test the AERMOD model in predicting the distribution of TSP, SO2, NOx, Hg parameters in PT. X East Java. The source of emissions produced comes from production process activities and supporting activities. By using AERMOD View Software, dispersion simulations can be calculated. The data used in modeling the distribution of emissions of PT. X is meteorological data (wind direction/speed, surface temperature, air humidity, atmospheric pressure, exposure to solar radiation, atmospheric cover, etc.), Hourly Surface Met Data in Sidoarjo Regency from 2013 – 2022, and Upper Air Met Data in Sidoarjo Regency from 2013 – 2022. So the results obtained are SO2 parameters of 3.47 ug / m3, NOx parameters of 17.8 ug / m3, TSP parameters of 2.310 ug / m3, parameters Hg of 0,0024 ug/m3